Oxygen functionalized porous activated biocarbons with high surface area derived from grape marc for enhanced capture of CO2 at elevated-pressure. (30th April 2020) - Ismail, Intan S.; Singh, Gurwinder; Smith, Paul; Kim, Sungho; Yang, Jae-Hun; Joseph, Stalin; Yusup, Suzana; Singh, Mandeep; Bansal, Vipul; Talapaneni, Siddulu N.; Vinu, Ajayan
Abstract: This research demonstrates the conversion of grape marc into highly carbonaceous and oxygen functionalized porous activated biocarbons (PABs) with a high specific area for CO2 capture. The materials are synthesized using KOH activation at 800 °C and show a high content of micropores and high specific surface areas which can be easily manipulated by varying the amount of KOH. The optimized material PAB3 obtained using KOH/grape marc biochar ratio of 3 displays the highest specific surface area (2473 m 2  g −1 ), high micropore volume (0.72 cm 3  g −1 ) and a pore diameter of 0.74 nm. Owing to its highly developed porosity and excellent textural parameters, PAB3 exhibits a high CO2 adsorption of 6.2 mmol g −1 at 0 °C/1 bar and 26.8 mmol g −1 at 0 °C/30 bar. It is often considered challenging to synthesize a CO2 adsorbent with all-round performance for CO2 capture under diverse conditions of temperature and pressure. The optimized material PAB3 is also found to be thermally stable which when coupled with its superior CO2 capture performance presents a promising candidature in the field of carbon capture. Furthermore, the excellent features of the synthesized material suggest that these materials could be extended to several other adsorption related fields. Graphical abstract: Image 1